Strengthening women’s resilience and participation in climate governance in the agri-food sector through public policies - Mohammed, Kamaldeen; Najjar, Dina; Bryan, Elizabeth (International Center for Agricultural Research in the Dry Areas, 2023)
Women are vulnerable to adverse climate change impacts and their active involvement and decision-making in the climate change and agrifood governance is limited, especially in the Global South. New research based on a strategic review of literature conducted as part of CGIAR research initiative HER+: Harnessing gender and social equality for resilience in agrifood systems indicate that public policies are vital instruments towards improving women’s participation in climate change governance and enhancing their resilience.